(untitled) (Research, Society and Development, 2020)
This work aimed to verify the effect in vitro, of Ascophyllum nodosum (AN) seaweed extract on the morphology and cellulolytic capacity of the fungus Fusarium oxysporum f. sp. vasinfectum (FOV). Thus, the fungus was placed in contact with different doses of the extract, being these: 0, 0.5, 1.0, 2.0, 4.0 and 8.0%. It was verified that the product, with increasing doses, progressively induced mycelial growth of the fungus, as measured by the diameter of the colonies and fresh mass of mycelium grown in PD (potato-dextrose) culture medium. This result was also corroborated by the progressive increase in the activity of the β-1,3-glucanase and chitinase enzymes required during the hypha elongation process. However, the AN extract progressively reduced FOV sporulation with increasing doses. Furthermore, the cellulolytic capacity of the phytopathogen was significantly reduced in the presence of the algae extract, which was measured by the activity of the enzymes endo-β-1,4-glucanase, exo-β-1,4-glucanase and β-glucosidase. Thus, these facts constitute important information for the management of fusariosis, since the inhibition of sporulation and decreasing degradation capacity of the cellulose by the pathogen, can translate into declined disease in compatible host-pathogen interactions.